PENGEMBANGAN BOOKLET DENGAN PENDEKATAN SAINTIFIK MATERI SIKLUS HIDUP HEWAN UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS IV PADA MATA PELAJARAN IPA - Wiratna Immanuel imm; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar (Kapedas), 2022)
The purpose of this study was to produce booklet learning media, to determine user responses and to determine the effectiveness of booklet learning media with a scientific approach to animal life cycle material to improve student learning outcomes. The type of research used is the development (Research and Development). The research model in the development of learning media is the ADDIE model. The types of data used are qualitative and quantitative data using interview instruments, need analysis questionnaires, questions, expert validation and user response questionnaires. Based on the results of the study, it can be concluded that the learning media used is appropriate to be used as a medium for learning natural sciences for class IV animal life cycle material. The results of the validation of material experts are 80%, the results of the validation of linguists are 80%, and the results of the validation of media experts are 70%. From the results of user responses to the booklet media, it is very good according to the results of student questionnaire analysis from aspects of attention 70%, aspects of interest 81%, aspects of confidence 76%, and aspects of satisfaction 62%. Based on the results of the t-test with tcount = 0.34 > ttable of 0.012, then Ho can be accepted. So it can be concluded that booklet media can improve the learning outcomes of fourth grade students at SDN 102 North Bengkulu.